The Influence of Social Media Marketing on Donation Intention with Brand Image and Brand Trust as Mediation - Selvy Dian Nita; Soepatini Soepatini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of social media marketing on donation intentions with the mediation of brand image and brand trust. This study uses a quantitative method with the SEM-PLS analysis approach, involving 171 respondents who are active social media users but have never donated through Kitabisa.com. Data were collected through an online questionnaire. The results of the study show that social media marketing has a significant effect on brand image and brand trust. Social media marketing also has a significant effect on donation intentions. Brand trust has a significant direct effect on donation intentions, while brand image does not show a significant direct effect. In addition, brand trust is proven to be a significant mediator between social media marketing and donation intentions, while brand image does not have a significant mediation effect.